2017
DOI: 10.1017/s1047951117000440
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of health-related quality of life in children with chronic heart disease

Abstract: Beyond medical treatment, integration into school is important to increase health-related quality of life in children and adolescents surviving with chronic heart disease. Regular screening of health-related quality of life is recommended to identify patients with special needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 56 publications
3
10
0
1
Order By: Relevance
“…In short, this study revealed high levels of quality of life in children and adolescents with CHD, which is consistent with the predominance of simple CHD in this sample. These results are in line with those of Ernst et al (2018) and Niemitz et al (2017) who found that patients with severe heart disease and greater need for medical care have worse quality of life. The 5-month data collection period proved insufficient to develop the validation process, as mentioned above.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In short, this study revealed high levels of quality of life in children and adolescents with CHD, which is consistent with the predominance of simple CHD in this sample. These results are in line with those of Ernst et al (2018) and Niemitz et al (2017) who found that patients with severe heart disease and greater need for medical care have worse quality of life. The 5-month data collection period proved insufficient to develop the validation process, as mentioned above.…”
Section: Discussionsupporting
confidence: 90%
“…The perception of quality of life varies from person to person, across families. For this reason, it is important to assess the personal perspective of each child or adolescent and their parents (Marino, Cassedy, Drotar, & Wray, 2016;Niemitz et al, 2017). The analysis of the characteristics of the quality of life of children/adolescents with CHD is of undeniable interest because it will allow identifying the impact of the disease and/ or treatments and better understanding patients, their evolution, and adaptation to the disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bei herzkranken Kindern, Jugendlichen und Erwachsenen sind die funktionellen Aspekte der körperlichen Funktionsfähigkeit, der psychomotorischen Entwicklung, des psychischen Befindens und der sozialen Funktionsfähigkeit die maßgeblichen Schlüsselfaktoren für die QoL [44,52]. So wurde über alle Altersgruppen eine Korrelation zwischen reduzierter QoL und Schwere der Herzerkrankung, Komplexität und Häufigkeit medizinischer Maßnahmen, aber auch reduziertem Selbst-wertgefühl und vermehrten Verhaltens-und emotionalen Problemen einschließlich Fehlzeiten in der Schule gefunden [52,64]. Exekutive Dysfunktionen, soziale Wahrnehmungsstörungen, reduzierte schulische Leistungen und internalisierende Störungen wie Depression oder Angst sind signifikant mit verminderter QoL assoziiert [44].…”
Section: Zusammenhänge Zwischen Entwicklungsmustern Und Lebensqualitätunclassified